Analysis and interpretation of power auto-transformer winding axial displacement and radial deformation using frequency response analysis. (July 2020) - Mahvi, Mojtaba; Behjat, Vahid; Mohseni, Hossein
Highlights: Frequency range between 1–100 kHz is mainly affected by the mechanical faults. 1 st resonance of the autotransformer DPF remains unchanged during mechanical faults. The low and high frequency range are mainly affected by axial and radial faults. The mid frequencies are influenced by both axial and radial faults. The crest factor is likely to be capable of diagnosing of fault type. Abstract: Frequency response analysis (FRA) is a sensitive method established for testing the mechanical integrity of transformers. However, interpretation of FRA signature still requires specialist's advice, while FRA interpretation codes have not been approved officially. In order to improve interpretation of FRA test, different types of mechanical faults with various extents are required to be tested on power transformers. So, the main objective of this paper is to investigate the capability of detecting the type and severity of winding mechanical failure using interpretation of FRA test results. To this end, the extracted FRA signatures of 3D FEM based various radial deformations, axial displacements and also simultaneous radial-axial deformations were compared using two existing statistical indicators namely DABS and ASLE. The study demonstrated that frequency range between 1 and 100 kHz is mainly affected by the mechanical faults and the 1st resonance of the double-peak feature of the auto-transformer FRA remains unchanged during winding mechanical faults. The analysis of the simultaneous fault showed that the low and high frequency signatures are mainly affected by axial and radial deformations, respectively and the mid frequencies are influenced by both faults. For fault type detection two new condition indictors viz. the crest factor and frequency center were proposed for the first time and they were calculated based on ratio of the real to imaginary part of the FRA signature which implicitly contains both the FRA amplitude and phase information. The results showed that the crest factor is likely to be capable of diagnosing of fault type.